Impact of mandibular third molar extraction in the second molar periodontal status: A prospective study - Paulo Eduardo Melo Stella; Saulo Gabriel Moreira Falci; Lorrayne Estéfane Oliveira de Medeiros; Dhelfeson Willya Douglas-; Patricia Furtado Gonçalves; Olga Dumont Flecha; Cássio Roberto Rocha Dos Santos (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of the present study was to assess the periodontal condition and sensitivity of second mandibular molars after the extraction of the adjacent third molar, while also assessing the quality of life of the patients. Materials and Methods: Twenty-three healthy patients were assessed in terms of probing depth, gingival height, gingival thickness, dental sensitivity, plaque index and bleeding on probing (adjacent second mandibular molar), before the surgical procedure, as well as 60 and 180 days after the surgery. The following data were also recorded and measured: the position and size of the impacted teeth; the size of the alveoli after surgery and the quality of life of the patient. Results: Significant differences were found for probing depth and gingival height before and after 180 days. The plaque index increased significantly after surgery (P = 0.004), as did bleeding on probing. No significant difference was found for the quality of life. The size of the third molar extracted was correlated with bleeding on probing 180 days after the surgery. Conclusion: An improvement was noted in the periodontal condition of the second mandibular molars after the extraction, based on the assessments of probing depth and gingival height. The position of the third molar affected the periodontal condition of the second mandibular molar. No alterations were recorded for dental sensitivity or the quality of life after the extraction.